2017
DOI: 10.1371/journal.pone.0171053
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping-by-Sequencing in a Species Complex of Australian Hummock Grasses (Triodia): Methodological Insights and Phylogenetic Resolution

Abstract: Next-generation sequencing is becoming increasingly accessible to researchers asking biosystematic questions, but current best practice in both choosing a specific approach and effectively analysing the resulting data set is still being explored. We present a case study for the use of genotyping-by-sequencing (GBS) to resolve relationships in a species complex of Australian arid and semi-arid grasses (Triodia R.Br.), highlighting our solutions to methodological challenges in the use of GBS data. We merged over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 67 publications
(100 reference statements)
5
56
0
Order By: Relevance
“…Largely on the basis of previous investigations of the Triodia basedowii complex and close relatives (Anderson et al 2016(Anderson et al , 2017, and in conjunction with additional morphological measurements for the current study, we found evidence to support the recognition of eight new species, four of which are largely restricted to the Pilbara region of Western Australia. A taxonomic account of the group is provided in the following section.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Largely on the basis of previous investigations of the Triodia basedowii complex and close relatives (Anderson et al 2016(Anderson et al , 2017, and in conjunction with additional morphological measurements for the current study, we found evidence to support the recognition of eight new species, four of which are largely restricted to the Pilbara region of Western Australia. A taxonomic account of the group is provided in the following section.…”
Section: Resultssupporting
confidence: 84%
“…In cases where morphological characters between two or more species overlap, ITS sequences from Anderson et al (2016) were used to make diagnoses clearer. Genomic divergences estimated from distance-based clustering and phylogenetic branch lengths (Anderson et al 2017) were evaluated in the context of previous morphological and genetic work on the complex (Anderson et al 2016). Taxa that showed strong evidence for distinction (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RADseq has also been successfully employed to tease apart the inter-and intraspecific relationships of a recently diversified clade of Heliconius butterflies (Nadeau et al, 2013). However, the extent to which such data are useful for inferring phylogenetic relationships in plant species complexes has been little studied (Anderson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%